Shunt Lesions Part I: Patent Ductus Arteriosus, Atrial Septal Defect, Ventricular Septal Defect, and Atrioventricular Septal Defect. (August 2016) - Backer, Carl L.; Eltayeb, Osama; Mongé, Michael C.; Mazwi, Mjaye L.; Costello, John M.
Abstract : Objectives: This review summarizes the current understanding of the pathophysiology and perioperative management of patent ductus arteriosus, atrial septal defect, ventricular septal defect, and atrioventricular septal defect. Data Source: MEDLINE and PubMed. Conclusions: The four congenital cardiac lesions that are the subject of this review, patent ductus arteriosus, atrial septal defect, ventricular septal defect, and atrioventricular septal defect, are the most commonly found defects causing a left-to-right shunt. These defects frequently warrant transcatheter or surgical intervention. Although the perioperative care is relatively straightforward for many of these patients, there are a number of management strategies and complications associated with each intervention. The treatment outcomes for all of these lesions are very good in the current era.